Monitoring of the prokaryotic diversity in pit mud from a Luzhou‐flavour liquor distillery and evaluation of two predominant archaea using qPCR assays. Issue 3 (15th April 2014) - Luo, Qingchun; Liu, Chaolan; Wu, Zhengyun; Wang, Haiying; Li, Wenfang; Zhang, Kaizheng; Huang, Dan; Zhang, Jing; Zhang, Wenxue
<x xml:space="preserve">Abstract</x> Pit mud plays a crucial role in the production of the Luzhou‐flavour liquor. Its quality directly determines liquor quality and yield. The aged pit mud produced good quality liquor but aging pit mud did not. The aim of this work was to investigate the prokaryotic diversity of the aged and aging pit mud from a Luzhou‐flavour liquor distillery using molecular methods. Two bacteria‐specific and two archaea‐specific 16S rRNA gene clone libraries were constructed and analysed using amplified ribosomal DNA restriction analysis. A total of 273 clones were studied, which resulted in 28 operational taxonomic units. Bacteroidetes and Firmicutes predominated in both the aged and aging pit mud, but Synergistetes and Actinobacteria were only detected in the aged pit mud. The family Methanosaeta dominated in the aged pit mud, while the Methanosarcina predominated in the aging pit mud. These results were confirmed using two genus‐specific quantitative real time PCR assays. This research distinguished microbial community structure in the aged and aging pit mud for the first time, and has laid an initial foundation for identifying good quality pit mud and for maintaining the quality of pit mud. Copyright © 2014 The Institute of Brewing & Distilling